High dietary salt intake correlates with modulated Th17-Treg cell balance resulting in enhanced bone loss and impaired bone-microarchitecture in male mice - Hamid Y. Dar (Nature Portfolio, 2018)
Abstract Osteoporosis is associated with reduced density and quality of bone leading to weakened skeleton thereby increasing the risk of fractures responsible for increased morbidity and mortality. Due to preference for western food style the consumption of salt intake in our diets has increased many folds. High dietary salt intake has recently been linked with induction of Th17 cells along with impairment of Treg cells. Also, Th17 cells have been one of major players in the pathophysiology of various bone pathologies including osteoporosis. We thus hypothesized that high salt diet (HSD) intake would lead to enhanced bone loss by modulating Th17-Treg cell balance. In the present study, we report for the first time that HSD intake in male mice impairs both trabecular and cortical bone microarchitecture along with decreasing the mineral density and heterogeneity of bones. The HSD modulates host immune system and skews Treg-Th17 balance by promoting osteoclastogenic Th17 cells and inhibiting development of anti-osteoclastogenic Treg cells in mice. HSD also enhanced expression of proinflammatory cytokines (IL-6, TNF-α, RANKL and IL-17) and decreased the expression of anti-inflammatory cytokines (IL-10, IFN-γ). Taken together the present study for the first time establishes a strong correlation between high dietary salt intake and bone health via interplay between Th17-Treg cells.